Tracing the Jerusalem Code : Volume 1: The Holy City Christian Cultures in Medieval Scandinavia (ca. 1100–1536) - Aavitsland, Kristin B.; Bonde, Line M. (2021)
With the aim to write the history of Christianity in Scandinavia with Jerusalem as a lens, this book investigates the image – or rather the imagination – of Jerusalem in the religious, political, and artistic cultures of Scandinavia through most of the second millennium. Jerusalem is conceived as a code to Christian cultures in Scandinavia. The first volume is dealing with the different notions of Jerusalem in the Middle Ages.